Addition of whey protein to fresh cheese. - Arce-Méndez, José Rafael; Thompson-Vicente, Eduardo; Calderón-Villaplana, Sandra (Agronomía Mesoamericana, 2015)
This work has been conducted in order to assess the effect of adding whey protein (WP) to fresh cheese. The yield, proximal chemical composition, tryptophan content,and texture and consumer sensorial acceptance were obtained. The study was conducted at a cheese factory located in San Carlos, Costa Rica, in 2011. The protein obtained from whey was added during the cheese manufacturing process, before adding the microbial rennet; and four enrichment levels were evaluated, including one control. The supplemented cheese showed an acceptance rating between 6.8 and 7.1. Products with 75 and 120 g of added whey protein per kilogram of milk showed no significant differences versus non-supplemented cheese, while the preference towards the cheese with 150 g WP/kg was less than that of the control (p<0.05). A cluster analysis revealed the existence of two consumer groups: one, accounting for 65% of the members of the panel, whose preference was unaffected by the protein supplemented; and, the other group where the added protein affected their liking negatively. Adding whey protein to the cheese resulted in a significant increase in yield and in the protein-to-water ratio, as well as a reduction in fat content (p<0.05). Nevertheless, there were structural changes in the cheese that caused the reduction of certain texture properties, generating changes in their sensory properties that reduced the preference of a representative group of consumers towards the product.